Trust oriented decision making via POMDPs - Aravazhi Irissappane, Athirai (2016)
Trust has been recognized as a vital concept in open MultiAgent Systems (MASs), where autonomous agents interact with each other in order to fulfil their designed objectives. In MASs, agents often need to rely on the abilities, competencies or knowledge of other agents (whose intentions are often unknown) for the fulfilment of their own goals. By relying on others, agents place their own interests at risk, as the other agents may be self-interested, diverse or deceptive, thus introducing the need for trust. In these scenarios, agents can evaluate the trustworthiness of potential interaction partners, using which they can make decisions about whom to interact with. While we see that it is necessary for agents to decide whose trustworthiness should be evaluated, which agent should be chosen as an interaction partner, etc., it is also vital to make these decisions in an optimal manner, as every agent strives towards maximizing its utility in the system.